2021
DOI: 10.3390/foods10071670
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Elements and the Quality of Mānuka (Leptospermum scoparium) Honey

Abstract: Soil properties in the foraging range of honeybees influence honey composition. We aimed to determine relationships between the antimicrobial properties of New Zealand mānuka (Leptospermum scoparium) honey and elemental concentrations in the honey, plants, and soils. We analyzed soils, plants, and fresh mānuka honey samples from the Wairarapa region of New Zealand for the chemical elements and the antimicrobial activity of the honey as indicated by methylglyoxal (MGO) and dihydroxyacetone (DHA). There were sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…The chemical composition of K. robusta and L. scoparium differed from the pasture, which contained higher concentrations of macronutrients and lower concentrations of micronutrients than the Myrtaceae species (Figure 1). However, non-essential trace elements, that may have had a negative effect on plant growth, were similar to or lower than those found elsewhere in L. scoparium [62], K. robusta [63], and pasture [47], which is consistent with the low application rates of these elements (Table 1). Values are geometric means and standard deviation ranges (n = 17).…”
Section: Plant Growth and Chemistrysupporting
confidence: 86%
See 1 more Smart Citation
“…The chemical composition of K. robusta and L. scoparium differed from the pasture, which contained higher concentrations of macronutrients and lower concentrations of micronutrients than the Myrtaceae species (Figure 1). However, non-essential trace elements, that may have had a negative effect on plant growth, were similar to or lower than those found elsewhere in L. scoparium [62], K. robusta [63], and pasture [47], which is consistent with the low application rates of these elements (Table 1). Values are geometric means and standard deviation ranges (n = 17).…”
Section: Plant Growth and Chemistrysupporting
confidence: 86%
“…Variables that were significantly correlated with TMW irrigation rates (Table 1- There was a significant negative correlation between the heights of K. robusta and L. scoparium and their foliar Na concentrations (Table 4, Figure 2). The foliar concentration of Na was two to three times higher than those reported in naturally established stands of L. scoparium [62]. Similarly, they were up to five and eight times higher than in K. robusta and L. scoparium grown in pot experiments, respectively [18,64].…”
Section: Plant Growth and Chemistrymentioning
confidence: 57%
“…Dihydroxyacetone (DHA) is the precursor to methylglyoxal ( Smallfield et al, 2018 ). Manuka phytochemicals including DHA were related with elements of the soil ( Meister et al, 2021 ) Nectar chemical traits were different between sites, but plant-to-plant variation within sites were the largest ( Icon et al, 2021 ). DHA varied from 32.1 to 133.7 mg/kg in the Ecuadorian pot-honeys, another botanical source is producing it because manuka is not growing in Ecuador.…”
Section: Resultsmentioning
confidence: 99%
“…However, caution needs to be applied as some nutrients and micro-essential elements may also arise from anthropogenic activity; for example, Cu is reported to be correlated to Cd in regions of agricultural practice [ 14 ]. A recent study by Meister et al found no correlations between elemental concentrations in honey and soil in a set of mānuka honeys from New Zealand [ 15 ]. This is in contrast with studies from other geographical origins and floral sources [ 16 ].…”
Section: Introductionmentioning
confidence: 99%